The Diccionario Inglés-Español de Contabilidad: Traducción and the Diccionario Inglés-Español de Contabilidad: Traducción de Frases y Expresiones: Two Specialised Dictionaries for Translating Terms and Collocations - Fuertes-Olivera, Pedro A.; Nielsen, Sandro; Bergenholtz, Henning (MonTi Monografías de Traducción e Interpretación, 2015)
This paper focuses on the role dictionaries play in a translation situation. This role is analysed in terms of the tenets of the Function Theory of Lexicography, which proposes that users do not have needs in general but punctual needs in specific situations. For example, translators of accounting texts need insertable equivalents whose meanings and language behaviour are clearly described. Furthermore, translators also need contextual data on domain-specific consensual usage. The construction of the Accounting Dictionaries and Diccionarios de Contabilidad reveals that the Function Theory offers theoretical and practical solutions for constructing dictionaries that target user needs in a precise way (Fuertes-Olivera & Tarp 2014). For example, two recent accounting dictionaries, the Diccionario Inglés-Español de Contabilidad: Traducción and Diccionario Inglés-Español de Contabilidad: Traducción de Frases y Expresiones, offer precise dictionary data for disambiguating the meaning of English accounting terms, their Spanish equivalents and their use in real English and Spanish accounting texts.